Arithmetics in the early years of fundamental education through a mathematics workshop about division with TDICs - Claudia de Oliveira Lozada; Sidney Leandro da Silva Viana; Marcos Lucas da Silva Oliveira; Bruna Gama dos Santos; Cryslane de Araújo Lima; https://orcid.or 0002-1638-1499 (Universidade Estadual de Alagoas, 2021)
The mastery of basic arithmetic operations by students in the early years of elementary school, whether conceptual or procedural, is still below expectations in macro-evaluations. In order to achieve satisfactory levels of proficiency, it is essential to promote the development of the skills and competences necessaryto understand operations and their applications in daily life. The simple operationalization of the methods of solving these operations by practical procedures and the neglect with the understanding of the algorithms can considerably affect the learning of other contents in which the operations are used. Furthermore, the difficulties that arise due to the lack of mastery of these operations in the initial years drag on through the final years of elementary school to high school, showing that it is important for teachers to review their teaching practices. However, teachers in the early years of elementary school, the stage of schooling where arithmetic operations are primarily developed, also encounter difficulties in understanding these operations and teaching them can be a challenge, at the same time as it may involve adopting approaches mistakes that lead to misunderstanding without actually learning. Among arithmetic operations, the division operation, whether exact or inaccurate, is still one of the operations in which both teachers in the early years of elementary school and students have difficulties, as well as the subtraction operation. In order to improve the understanding of the exact and inaccurate division algorithm in the early years of elementary school, a workshop was offered in 2019 for teachers and prospective teachers. The results show that the difficulties are concentrated in the special cases of division and in the inaccurate division.